0

# Simplify using distributive property3(-2+x+4)

you have to use distributive property

### 3 Answers by Expert Tutors

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...
4.8 4.8 (4 lesson ratings) (4)
0
Better Simplify the parenthesis first. It becomes important when things get more complicate.

3 ( -2 + X + 4 ) = 3 ( X + 2) = 3X + 6

Like:

5 - 3 ( -95 + 75 + X)= 5 - 3 ( -15 + X) = 5 + 45 -3X = 50 -3x

You don't have to multiply 3 by 95& 75.
Beth L. | Patient, Knowledgeable and Very Qualified Mathematics TutorPatient, Knowledgeable and Very Qualifie...
0
3 (-2 + x + 4) = -6 +3x +12 = 3x + 6
Multiply the three through (above) then add the -6 to the +12.

3x + 6  is your final answer.

Ralph L. | Algebra I, II, Visual Basic, Beginning C++ tutorAlgebra I, II, Visual Basic, Beginning C...
4.0 4.0 (1 lesson ratings) (1)
0

distributive property states:  a(b + c) = ab + ac

3(-2 + x + 4)

in your case you have three values inside the parentheses, so you can use this:

a(b + c + d) = ab + ac + ad

so, (3 * -2 + 3x + 12) ---> -6 + 3x + 12 ---> 3x + 6